Penanganan Pengungsian Dan Pencari Perlindungan Oleh Lembaga Di Rumah Detensi Imigrasi (RUDENIM) Pusat Tanjungpinang Tahun 2023-2024 - Kustiawan Kustiawan; Ramadiyati Okta Putri; Siti Hidayah; Dea Putri Rahmadhani; Dwi Aprilia; Yunisya Azura (CV. ITTC INDONESIA, 2025)
This scientific paper aims to discuss the handling of refugees and asylum seekers at the Tanjungpinang Central Immigration Detention Center (RUDENIM) in 2023-2024. The approach of this research is qualitative by collecting data through in-depth interviews and observations at RUDENIM. The results of the study show that RUDENIM strives to provide the best protection and service despite experiencing various obstacles. Some of the main obstacles include limited facilities, insufficient human resources, and limited capacity. In addition, long-term detention and lack of psychological facilities are also major challenges for refugees. RUDENIM works closely with international organizations such as UNHCR and IOM to ensure basic needs, such as food, shelter, and health services, are met. However, there is still a need for improved coordination between related agencies and improvements in terms of facilities and management so that refugee rights can be protected.